(untitled) - Gilman, Nicholas Paine (Boston, 1889)
This book introduces about product sharing, the wages system in its various forms, the father of profit sharing and his house, the profit sharing system on the continent, profit sharing in transportaion, distribution, and agriculture, industrial partnerships and profit sharing in England, American experience in profit sharing, past profit sharing, summary and analysis of experience in profit sharing.
Keywords: Chia sẻ lợi nhuận,Profit-sharing